When we raise something to a power, it really justs means we are multiplying it by itself. 3^2 (3 to the power of 2) means that we are mutliplying 3 by itself: 3•3 = 9 or 3^2 = 9 (there are two 3's)
However, when we rasie something to the 0 power, it equals 1. That is because we are multiplying it by itself 0 times. We are not multiplying it by zero, we are effectively doing nothing at all. 3^0 = 1
6x^3+8x^2-10x-4 multiplied
Answer:
9
Step-by-step explanation:
To make the input-output table, we need to plug in the given vaues of x's in the equation to get their corresponding values of y.
Let's plug in x = -2 in y = 6x +5. So,
y = 6( -2) + 5 = -12 + 5 = -7
Similarly for x = 0, y= 6(0) + 5 = 5
For x = 1, y = 6(1) + 5 = 6 + 5 = 11
For x = 4, y = 6(4) + 5 = 24 + 5 = 29
For x= 5, y = 6(5) + 5 = 30 + 5 = 35.
I am attaching the input -output table from the above result.
Hope this helps you!
Answer:
D) 3x^2 - 12
Step-by-step explanation:
Using PEMDAS;
There is no need to evaluate the part of the equation (x^2 - 8) because is no need to, as it is already in its simplest form.
We must evaluate the part of the equation continuing with, "- (-2x^2+4)," as it is not in its simplest form.
Evaluating "- (-2x^2+4)":
Step 1: Distributing the negative
Once distributing the negative symbol amongst the values within the parenthesis according to PEMDAS, we get "2x^2 - 4" as the product.
Step 2: Consider the rest of the equation to evaluate
Since the part of the equation is still in play here as it is a part of the original equation to be solved, we must evaluate it as a whole to get the final answer.
Thus,
x^2 -8 + 2x^2 - 4 = ___
*we can remove the parenthesis as it has no purpose, since it makes no difference.
Evaluating for the answer, we get,
x^2+2x^2 + (-8 - 4) = 3x^2 - 12
Hence, the answer is D) 3x^2 - 12.